The Degree of Practicing Teachers in The Intermediate Stage In Afif Governorate in the Kingdom of Saudi Arabia of The Methods of Warning Against Bullying Under The Islamic Education - Al-Otaibi, Sarah Swailem; Al-Seef, Abdulmohsen Saif (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the degree of awareness of Islamic education teachers in the intermediate stage about the behavior of bullying and the degree of practicing Islamic education teachers in the intermediate stage of the methods of warning against bullying under the Islamic education The descriptive method and the questionnaire was used as a tool for the study. The sample of the study consisted of (50) teachers of Islamic education for an intermediate stage in Afif city, Saudi Arabia. The study reached a number of results, the most important of which are: Awareness of teachers with a very large average (4.16) on the problem of bullying and a very large degree of practice (4.75) on the methods of warning of bullying under the Islamic education were the most important recommendations: Training teachers to face and solving the problems of bullying, moreover inserting lessons about bullying in the Islamic education curriculum.
Keywords: Bullying; Islamic Education; Intermediate Stage